THE INHIBITION TEST OF FLAVONOID AND TANNIN IN NONI FRUIT (Morinda citrifolia Linn) COMPARED TO CEFTRIAXONE TOWARDS Escherichia coli IN VITRO - Tessa Swesty Islamia; Atik Sutisna; Hikmah Fitriani (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Escherichia coli is one of the causatives of infection agents. Noni fruit that contains the antibacterial ingredients was predicted as an alternative medicine to reduce the resistance of antibiotics. Noni fruit extract can inhibit the growth of Escherichia coli. The absence of research on the active substances contained in this fruit which plays a role in inhibiting the growth of Escherichia coli encourages the researcher to conduct this research.Methodology: The research was an experimental laboratory with post-test only control group design. The Escherichia coli grown on Mac conkey agar. Flavonoid and tannin in noni fruit (Morinda citrifolia Linn.) diluted with 3 concentrations, 50%, 70%, 100% and 2 control groups, positive control with ceftriaxone and negative control with Dimethylsulfoxide 10% (DMSO). The treatment group were incubated for 24 hours, then the inhibitory zone formed was measured in mm. Results: The Kruskall-Wallis test showed significant difference in all concentration. The results obtained from this research showed that the average of inhibition towards Escherichia coli on positive control (22.83 mm) had the largest inhibition zone among flavonoid 100% (18.83mm), flavonoid 70% (14.67 mm), flavonoid 50% (6 mm), tannin 100% (17.33 mm), tannin 70% (10.83 mm), tannin 50% (7.50 mm), and negative control (2 mm).Conclusion: Flavonoid and tannin in noni fruit (Morinda citrifolia Linn) were effective for inhibiting the growth of Escherichia coli. The 100% concentration is the most effective concentration that can be promoted as an alternative medicine.